1998
DOI: 10.1200/jco.1998.16.7.2426
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of dose-intensity with single-agent carboplatin in patients with epithelial ovarian cancer. London Gynaecological Oncology Group.

Abstract: We have shown that carboplatin can be delivered at an AUC of 12 for four courses without granulocyte colony-stimulating factor support, although significant hematologic toxicity occurs. Nonhematologic toxicities were not clinically significant. Carboplatin offers an opportunity to intensify cisplatin therapy, but a greater than two-fold increase in dose-intensity probably needs to be achieved before significant effects on survival will be produced and hematologic support will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 17 publications
1
44
0
1
Order By: Relevance
“…With specific regard to carboplatin dose intensity, two trials failed to show any significant survival benefit between patients treated with an areaunder-the-curve (AUC) of 4 or 8 (Jakobsen et al, 1997) or AUC 6 or 12 (Gore et al, 1998).…”
mentioning
confidence: 99%
“…With specific regard to carboplatin dose intensity, two trials failed to show any significant survival benefit between patients treated with an areaunder-the-curve (AUC) of 4 or 8 (Jakobsen et al, 1997) or AUC 6 or 12 (Gore et al, 1998).…”
mentioning
confidence: 99%
“…Dose-intense treatment (higher mg per m 2 per unit of time) has been found to improve the survival of patients with breast cancer and other cancers (Hudis et al, 1999;Citron et al, 2003). But most clinical trials among patients with OC have failed to show a survival advantage of dose-intense regimens (McGuire et al, 1995(McGuire et al, , 1996Conte et al, 1996;Jakobsen et al, 1997;McGuire, 1997;Gore et al, 1998). For example, the Gynecologic Oncology Group (GOG) compared patients treated with eight cycles of standard dose cisplatin and cyclophosphamide to those receiving four cycles of high-dose therapy.…”
mentioning
confidence: 99%
“…Given the unfavorable characteristics of our patient population (85% stage IIIc-IV; 78% G2-G3 tumors) our data seem encouraging as compared to the 5-year OS rate of 25-35% observed after standard chemotherapy regimens in patients with similar characteristics. [18][19][20][21][22][23] On the other hand, a comparison of our data with the results of standard-dose cisplatin-based chemotherapy remains difficult to interpret due to the fact that most patients in our series were enrolled in the HDC program in chemosensitive status. 24 Interestingly, we observed that in patients inoperable at first surgery (these patients underwent succesful IDS) and therefore endowed with a poor prognosis 25,26 the 5-year OS rate (54%) and the median OS (75 months) seem Days to: WBC Ͼ1 ϫ 10 9 /l 10.6 Ϯ 0.9 8.7 Ϯ 0.7 9.8 Ϯ 0. to be higher than those (5-year OS ranging from 22% to 35% with a median OS of 25 months) seen with standard chemotherapy.…”
Section: Discussionmentioning
confidence: 61%
“…Non-hematological toxicity: Two treatment-related deaths (3.6%) occurred in a 51-year-old (this patient received ABMT) and a 42-year old patient who developed candida sepsis and malignant hyperthermia, respectively. Data relative to non-hematological toxicity are detailed in Table 5 (18) Cardiac toxicity 55 (100) Neural toxicity 11 (20) 36 (65) 6 (10) 2 (4) Renal toxicity 36 (65) 16 (29) 3 (5) a Non-hematological toxicity was evaluated according to the WHO scale. There were 55 patients evaluable.…”
Section: Response and Survivalmentioning
confidence: 99%